2007
DOI: 10.1111/j.1365-2966.2006.11376.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic hydrogen atmosphere models and the neutron star RX J1856.5-3754

Abstract: RX J1856.5−3754 is one of the brightest nearby isolated neutron stars, and considerable observational resources have been devoted to it. However, current models are unable to satisfactorily explain the data. We show that our latest models of a thin, magnetic, partially ionized hydrogen atmosphere on top of a condensed surface can fit the entire spectrum, from X-rays to optical, of RX J1856.5−3754, within the uncertainties. In our simplest model, the best-fit parameters are an interstellar column density N H ≈ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 73 publications
7
153
0
Order By: Relevance
“…Model atmospheres with partially ionized hydrogen are compared to models computed by Ho et al (2007). We have found that our models are in a good agreement with these calculations.…”
Section: Methods Of Atmosphere Structure Calculationssupporting
confidence: 60%
See 1 more Smart Citation
“…Model atmospheres with partially ionized hydrogen are compared to models computed by Ho et al (2007). We have found that our models are in a good agreement with these calculations.…”
Section: Methods Of Atmosphere Structure Calculationssupporting
confidence: 60%
“…12 for illustration). Ho et al (2007) radiation (≈1.2%, , therefore it is possible to fit the radiation of this star by the single model atmosphere. Other XDINSs have larger pulse fractions, up to 18% (RBS 1223.…”
Section: Resultsmentioning
confidence: 99%
“…This result of spectral modelling (i.e the fitting with the condensed surface model with partially ionized, optically thin hydrogen atmosphere above it, including vacuum polarization effects) suggests a true radius of RX J0720.4−3125 of 13.3±0.5km for a standard neutron star of 1.4 solar mass, and indicates a stiff equation of state of RX J0720.4−3125 (for similar results, see also Ho et al 2007;Heinke et al 2006;Suleimanov & Poutanen 2006;Suleimanov et al 2011). Our model fits provide the angles between our line of sight and both the rotation axis and the magnetic field axes, we obtain 42 ± 3 • and 47 ± 6 • , respectively.…”
Section: Fittedmentioning
confidence: 54%
“…In particular, the observational determination of the gravitational redshift of an isolated neutron star (INS) can be used to put constraints on the theoretical models of superdense matter. This goal can be achieved, for instance, by modeling and analyzing the observed emergent spectrum of a thermally emitting, pulsating INS via rotational phase-resolved X-ray spectroscopy (Zavlin et al 1995;Motch et al 2003;Pérez-Azorín et al 2006;Zane & Turolla 2006;Ho et al 2007;Suleimanov et al 2010;Hambaryan et al 2011Hambaryan et al , 2014, also developed and successfully applied by us).…”
Section: Introductionmentioning
confidence: 99%
“…The XDINS optical fluxes usually exceed by a factor of ∼5 (or more) the extrapolation of the X-ray blackbody, and their optical spectra, when measured, seem to follow a Rayleigh-Jeans distribution (e.g., Kaplan 2008). The XDINS optical emission has been interpreted either in terms of a non-homegeneous surface temperature distribution, with the cooler part emitting the optical (e.g., Pons et al 2002), or of reprocessing of the surface radiation by a thin H atmosphere around a bare neutron star Ho 2007), or of non-thermal emission from particles in the star magnetosphere (Motch et al 2003). However, for the measuredĖ, magnetospheric emission would not be detectable, at least if an average optical emission efficiency of rotation-powered neutron stars (e.g.…”
Section: Introductionmentioning
confidence: 99%